If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -8 = 75 Reorder the terms: -8 + n = 75 Solving -8 + n = 75 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + n = 75 + 8 Combine like terms: -8 + 8 = 0 0 + n = 75 + 8 n = 75 + 8 Combine like terms: 75 + 8 = 83 n = 83 Simplifying n = 83
| 4-2y=2y+13 | | 5y-20=-45 | | 6k+5=23 | | 6x+3=4x-11 | | 4q-17=2q+17 | | 3(2m+11)=33 | | 2y+11=4 | | x(x+1)+(x+2)=90 | | 5p-6=2p+12 | | 19-15x+26=180 | | -6x-2=10 | | 6x+8x+10x=120/24 | | 11r-21+-2r=-42 | | -2(2x+10)=180 | | 2x+9-5x=-27 | | 3r-31+5r=9 | | 2x-5x=90 | | 50-12=-7x+5x | | 6/8=12/x | | 1/2x+3x=96 | | -2q+42=-6 | | 2(x+1)+2.5=38 | | 14x^2=131 | | 125/10+5.25x | | .5x-.6x+x-.25=4 | | 5x-17+2x=67 | | -3(b-8)-5=5(b+2)+1 | | n+3n-12=6 | | 8x^2+0x-50=0 | | 17-5m=20 | | r+-6.4=7.1 | | n-10n+22=-2 |